Farmers' Management Practices against Tomato Leaf Miner Tuta absoluta (Myrick) (Lepidoptera: Gelechiidae) in Surkhet, Nepal - Lamsal, K; Shapkota, R; Dahal, K C; Upadhaya, N; Khanal, D (Journal of the Plant Protection Society, 2022)
Tuta absoluta (Myrick) is one of the most destructive pests of tomato globally. In order to study its current status and management practices adopted by farmers, a household survey was conducted in February 2019 at three road corridors (Surkhet-Jumla, Surkhet-Dailekh and Surkhet-Jajarkot) and Birendranagar valley of Surkhet district. Amongst the tomato growers listed at the government offices and local key informants, a purposive random sampling method was employed to select the 60 tomato producers, 30 from Birendranagar Municipality, 15 from Barahatal Municipality (Surkhet-Jumla), 10 from Bheriganga Municipality (Surkhet-Jajarkot) and 5 from Gurans Municipality (Surkhet-Dailekh). Majority of tomato growers (52%) claimed T. absoluta as their major pest and most of them well aware about the symptoms of the pest in leaves as well as fruits. Majority of the farmers were found to be (33%) relied on chemical means while 27% on cultural methods, 18% used tomato leaf miner lure (TLM lure), 13% used botanicals, 5% used physical, and 3% used mechanical method for the management of T. absoluta. Chemicals means being very quick and more effective to other techniques in solitary were practiced by many but without reading the label, without measuring before use (57%), without any protective wear (53%) and lack of know-how on waiting period (78%). Most of the farmers having dependent on Agrovets (85%) for technical assistance were bound to continue the false practices. The efficacy of extension was found to be very poor exhibiting the urgency of pesticide use literacy for the farmers and the knowledge of IPM for pest management. Farmers should be taught about the harmful effects of chemical pesticides, methods of handling pesticides, use of protective gears and keep chemical as last resort. Other alternative means like use of TLM lures, botanical pesticides, use of nets etc. should be encouraged.